Fintech adoption among Generation-Z in Malaysia - Chan, Jian You; Chin, Chen Hun; Koo, How Shen (2024)
Fintech is defined as a new financial industry that includes technology application to improve financial activities (Schueffel, 2016). Besides that, Fintech is also known as any innovations that improve financial service processes by proposing technology solutions into distinct business situations (Leong & Sung, 2018). With the advancement of technology, technology integration is prevalent in the financial industry (Jourdan et al., 2023). There are various innovations emerge in the financial industry that have incorporated technology such as mobile payment, peer-to-peer lending, robo-advisory, insurance technology and crypto-assets have made financial services more accessible and convenient to consumers (Feyen et al., 2021). One of the advantages and benefits of fintech is financial inclusion where everybody is given chances to access to financial services such as banking, payment and lending services without concerns on travelling (Venet, 2019). Fintech also provides cost-effective financial solutions compared to traditional financial services at the standpoints of owner as well as customer. From the standpoint of owner, fintech helps to eliminate cost spent on physical financial institution branches while leveraging digital platforms to reduce overhead costs (Nik Herda & Tye, 2023). In terms of risk management and compliance, fintech incorporates artificial intelligence (AI) to improve risk management and strengthen security measures so that the likelihood of financial fraud can be significantly reduced at the same time increasing consumer confidence on the financial system (Morshadul Hasan & Ariful Hoque, 2023). There is lack of empirical research on the topic that mainly focuses on the GenerationZ in Malaysia where existing studies focused on millennials instead of Generation-Z. (Vaicondam, Jayabalan, Tong, Qureshi, & Khan., 2021). Besides, several studies that researched about Gen-Z in Malaysia focused on the accounting sector or solely based on ewallet (Rosli, Saleh, Md. Ali & Abu Bakar., 2023; Azhar, Zakaria, Foo, & Aziz., 2023). In short, the purpose of this study is to investigate fintech adoption among Malaysia's Generation-Z population in order to fill a research vacuum left by prior studies.